1986
DOI: 10.1007/bf01886732
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival following relapse after 5-FU but not CMF adjuvant breast cancer therapy

Abstract: Beginning in 1974, patients with greater than or equal to 4 nodes positive following mastectomy were randomized to receive either 5-FU i.v. weekly or CMF i.v. every 2 weeks, both given for 12 months. Median follow-up now exceeds 112 months with nine year results below: (table; see text) Early results based on relapse-free survival favored CMF, but more patients currently are alive on the 5-FU arm. As the survival curves cross at 40 months, the 20% survival advantage for 5-FU did not achieve statistical signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 26 publications
2
49
1
Order By: Relevance
“…In addition to adjuvant therapy, be it CTx, hormone therapy, or immunotherapy with trastuzumab-type monoclonal antibodies, metabolic and endocrine factors related to an increase in weight gain after cancer diagnosis are strongly associated with higher risk of recurrence and reduction in survival rates 14,29,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adjuvant therapy, be it CTx, hormone therapy, or immunotherapy with trastuzumab-type monoclonal antibodies, metabolic and endocrine factors related to an increase in weight gain after cancer diagnosis are strongly associated with higher risk of recurrence and reduction in survival rates 14,29,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding post-diagnosis weight gain and prognosis [18][19][20][21][22][23][24] is not extensive and it is difficult to compare results across studies, because the studies often used different measures to evaluate prognosis. Some examined only overall survival, while others use disease-free, relapsefree or recurrence-free survival, and even among the latter three, definitions often vary across study.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the definition of recurrence endpoints between studies may account for our differing results. -14 -Of the remaining six studies on weight gain and prognosis [18][19][20][21][22][23], three reported no relationship [19;20;23], and none of the three that found a negative impact on prognosis [18;21;22], reported a statistically significant effect on recurrence or any outcome measure that included only breast cancer events. A study by Camoriano et al [18] of 545 node-positive women reported a significant effect of weight gain on overall survival, but not on recurrence; and only for premenopausal, but not post-menopausal, women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations